The Growth of Sport in Co. Tipperary, 1840-1880 - Bracken, Pat (Book collections on Project MUSE., 2018)
This book creates an important link between the pre-famine and post-famine era, in a way which has not been investigated previously, either nationally or locally. Using Tipperary as a county unit, this new approach to the growth of sport, in the pre-GAA era, also challenges the notion that hurling was a game of the past. The evidence from the research suggest otherwise. Sport was popular among all the classes, though there was a great emphasis on recreational sport among families in country houses and estates. Recreations practiced, reflected the games culture of the time in England. The book is very topical as it explores the rise and fall of various games countywide, indicating the fluid nature of sport and the ephemeral nature of play. It also demonstrates that there was a great awareness among the participants of the rules and laws of various activities. Some activities were constant throughout the era under review, notably horse racing and hunting to hounds. Indeed, information compiled from the contemporary press suggests that hunting to hounds was at its height in the county, prior to the onset of the Land Wars. All aspects of sport are covered from lawn games; water sports; field sports and equine events. The role of female activity in sport is a crucial part of the study. Overall, this book is a thorough assessment of sport in Tipperary, between 1840 and 1880, on a scale not previously undertaken for any other county in Ireland.